Education for the Gifted and Talented: Student teachers reflecting about autonomy, control, and pedagogical diagnostics in a self-designed workshop program for gifted schoolchildren - David Rott (Journal of the European Honors Council, 2019)
In German schools, gifted education becomes more and more relevant, but it is still rare